PERBANDINGAN METODE UNTUK ESTIMASI SELEKTIVITAS JARING INSANG - Sulaeman Martasuganda; Anraku Kazuhiko; Kawamura Gunzo; Matsuoka Tatsuro (Buletin PSP, 2009)
This research has been done in the Akime waters, Kagoshima, Japan. Spratelloides japonicas is the target fish of gillnet multifilament use in this research. 5 units of the gillnet multifilament 210D/4 with different value of mesh size were used in this research. This research was aimed to determine the difference of selectivity curve that had been calculated based on Sparre, Kitahara, and Matsuoka selectivity method.The result showed that Matsuoka and Kitahara’s selectivity curves were similar in terms of the shape and slope from each mesh size, whereas Sparre’s selectivity curve was different from Matsuoka and Kitahara’s curves.The results of the comparison between Kitahara and Matsuoka’s selectivity curve and length distribution curve from each mesh size showed that Kitahara and Matsuoka’s have close value of range between the length range of selectivity curve and the length range of caught fishes. Sparre’s method showed a significant difference between the length range of selectivity curve and the length range of caught fishes. From that results concluded that Kitahara and Matsuoka’s selectivity methods are accountable and Sparre’s method is unaccountable.Keywords : gillnet selectivity,Kitahara,Matsuoka's methods, size selectivity, Sparre et al.